Surveillance and Characterization of Drug‑Resistant Mycobacterium tuberculosis Isolated in a Reference Hospital from Argentina during 8 Years’ Period - Imperiale, Belén Rocío (2019)
Background: Argentina is considered a country with a middle tuberculosis (TB) incidence. However, according to the last national epidemiological report released in 2018, since 2013, the trends are steadily increasing. The aims of this study were to determine the drug‑resistance (DR), multi‑DR and extensively DR (MDR/XDR‑TB), and rifampicin resistance (RIF‑R) burden as a part of the local TB diagnosis (June 2010–August 2018); to detect the mutations associated to isoniazid (INH) and RIF‑R and their geographical distribution; and to analyze the lineage relationship among the genetic patterns of the isolates circulating in the community. Methods: Respiratory and extrapulmonary specimens were processed by Ziehl–Neelsen stain and cultured on specific media. Drug‑susceptibility testing of isolates was performed by the MGIT 960 and a colorimetric micro‑method. Mutations conferring DR were detected by Genotype and DNA sequencing. Results: The study showed a DR‑TB prevalence of approximately 20% of the isolated strains, while M/XDR‑TB‑and particularly RIF‑R‑affected more than 5.0% of the total amount of cases. DR geographical distribution revealed isolates carrying mutations in the inhA gene promoter region only constrained to three districts where it was also registered two same family relatives’ cases with the infrequent rpoB S522 L/Q mutation. The fact that most DR/MDR‑TB isolates were not grouped in genetic clusters suggested that these cases may mostly have occurred due to endogenous reactivation rather than recently transmission. Conclusion: According to the obtained results, it would be convenient, in highly MDR‑TB suspected individuals, to confirm phenotypically, the INH and RIF susceptibility detected by molecular tests.